PERSEPSI GURU TERHADAP PROGRAM ARTIFICIAL INTELLIGENCE (AI) DALAM KEGIATAN PEMBELAJARAN DI SMA NEGERI 1 INDRALAYA UTARA - Amirul mu'minin; Sri Artati Waluyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine how teachers perceive the Artificial Intelligence (AI) program in learning activities at SMA Negeri 1 Indralaya Utara. The study employs a qualitative approach using descriptive qualitative methods. Sampling techniques utilized purposive sampling with three informants. Based on the analysis results, it can be concluded that teachers' perceptions of the Artificial Intelligence (AI) program in learning activities at SMA Negeri 1 Indralaya Utara are positive, receiving strong support from teachers for the AI program in the learning process at school. The experience, benefits, impacts, and significant role of Artificial Intelligence (AI) assist students and teachers in exploring knowledge and aid in creating learning media efficiently and automatically.